Health-Promoting Compounds in Stevia: The Effect of Mycorrhizal Symbiosis, Phosphorus Supply and Harvest Time - Silvia Tavarini; Clarissa Clemente; Cecilia Bender; Luciana G. Angelini (Molecules, 2020)
This work aimed to establish the synergic role of arbuscular mycorrhizal fungi (AMF) symbiosis, phosphorus (P) fertilization and harvest time on the contents of stevia secondary metabolites. Consequently, steviol glycosides (SVglys) concentration and profile, total phenols and flavonoids as well as antioxidant assays, have been assessed in inoculated and no-inoculated plants, grown with or without P supply and collected at different growth stages(69, 89 and 123 days after transplanting).The obtained results suggest that the synthesis of stevia secondary metabolites is induced and/or modulated by all the investigated variability factors. In particular, AMF symbiosis promoted total SVglys content and positively influenced the concentration of some minor compounds (steviolbioside, dulcoside A and rebaudioside B), indicating a clear effect of mycorrhizal inoculation on SVglys biosynthetic pathway. Interestingly, only the mycorrhizal plants were able to synthesize rebaudioside B. In addition, P supply provided the highest levels of total phenols and flavonoids at leaf level, together with the maximum in vitro antioxidant activities (FRAP and ORAC). Finally, the harvest time carried out during the full vegetative phase enhanced the entire composition of the phytocomplex (steviolbioside, dulcoside A, stevioside, rebaudioside A, B, C. total phenols and flavonoids). Moreover, polyphenols and SVglys appeared to be the main contributors to the in vitro antioxidant capacity, while only total phenols mostly contributed to the cellular antioxidant activity (CAA). These findings provide original information about the role played by AMF in association with P supply, in modulating the accumulation of bioactive compounds during stevia growth. At the cultivation level, the control of these preharvest factors, together with the most appropriate harvest time, can be used as tools for improving the nutraceutical value of raw material, with particular attention to its exploitation as functional ingredient for food and dietary supplements and cosmetics.